Martial arts and school violence: Examining the potential of martial arts training to reduce or foster aggressive behaviour in schools - Brian Moore; Stuart Woodcock; Dean Dudley (International Journal of Educational Research Open, 2024)
School violence is of international concern. However, the evidence regarding school violence may underestimate its prevalence. Consequently it is critical to develop effective interventions to address school violence. This study examined a psychosocial intervention based around a 10-week martial arts training program to address aggression. Two-hundred and eighty-three (N = 283) secondary students aged 12–14 years (M = 12.76, SD=0.68) participated in the study, which was evaluated using a randomized controlled trial. Results found that the intervention did not reduce, nor increase aggressive behaviour. This was inconsistent with most previous findings examining the impact of martial arts training on aggression, and points to a more nuanced perspective that martial arts training may have a limited effect on aggressive behaviour. While further research regarding the impact of martial arts training on aggressive behaviour may be warranted, this study recommends caution before considering martial arts as an intervention strategy to reduce or regulate aggressive behaviour in adolescents.